Conceptual design of an impulse turbine and gas generator for a rocket engine turbopump - Schneider, Matthew Dylan (Stellenbosch : Stellenbosch University, 2025)
Schneider, M. D. 2025. Conceptual Design of an Impulse Turbine and Gas Generator for a Rocket Engine Turbopump. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/da903599-6e5f-488d-ab0d-52814d882653